Henry Fleming against his cowardice in The Red Badge of Courage - Purwanto, Bambang; Aimah, Siti (Universitas Negeri Semarang, 2018)
Language is a means of communication in Literature. People can understand and analyze any story by using language. They can also find out the content of story from different country. Readers can also compare story from one country to another country. They can also translate story from different country with their own mother tongue. One example is The Red Badge of Courage. We can get many lessons and ideas from this American novel. It is a war novel, which focus on American Civil War. Henry Fleming is one of main characters in the novel. Regarding to the history of Civil War, we still have many questions from the content of it. How about the main character‘s dreaming in civil war? Can his bravery influence to his friends? What is the moral value from this war novel? People can get many imaginations and lessons from the main character, Henry Fleming. Descriptive qualitative is a method in discussing this novel. Reading, understanding, and analyzing are the necessity things to do. The idea and opinions from novel and reference books are sources in getting idea. We can take this novel is as a zero to hero novel regarding to the main character‘s activities. All soldiers in his troop surprise when they see a brave-heart person, Henry Flaming. Furthermore, Henry shows that he can beat his cowardice to be a brave man. His wound is a proof of being a hero in his troop. His questions of being a brave soldier show up after he beats all trials in civil war. Self-confidence in Henry Flaming is a way to show that a soldier must have bravery in leading a troop.